Challenges in Building a Portal for Sensors World-Wide - Nath, Suman; Liu, Jie; Zhao, Feng (First Workshop on World-Sensor-Web (co-located with SenSys), 2006)
SensorMap is a portal web site for real-time real-world sensor data. SensorMap allows data owners to easily make their data available on the map. The platform also transparently provides mechanisms to archive and index data, to process queries, to aggregate and present results on a geocentric web interface based on Windows Live Local. In this position paper, we describe the architecture of SensorMap, key challenges in building such a portal, and current status and experience.